Diseases of the Pancreas Current Surgical Therapy - Beger, Hans Günther; Matsuno, Seiki; Cameron, John L.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
"Diseases of the Pancreas" is based on the latest comprehensive data about molecular mechanism of acute pancreatitis, chronic pancreatitis and pancreatic cancer. The diagnostic techniques including histology, radiology, sonography etc. are based on the sensitivity and specificity of the respective methods. Special focus is given to the indication and contraindication to surgical technqiues. It contains specific treatment modality and results for the first time after long-term outcome evaluation. Surgical techniques are displayed with colored sketches series.
Anatomy of the Pancreas -- Physiology and Pathophysiology of the Pancreatic Functions -- Clinical Standards of Diagnostic Measures -- Acute Pancreatitis -- Chronic Pancreatitis -- Pancreatic Cancer -- Endocrine Tumors of the Pancreas -- Periampullary Tumors -- Cystic Neoplasia of the Pancreas -- Congenital Anomalies of the Pancreas -- Pancreatic Injury -- Transplantation of the Pancreas -- Index.
Keywords: Surgery; Abdominal surgery; Minimally invasive surgery; Surgical transplantation; Surgical oncology; Gastroenterology .; Surgery; Abdominal Surgery; Minimally Invasive Surgery; Transplant Surgery; Surgical Oncology; Gastroenterology